FICTIONALIZING LOVE OF YOUNG MOSLEMS: A COMPARATIVE STUDY OF MALE-FEMALE RELATIONSHIP IN MIZWAR’S KIAMAT SUDAH DEKAT AND MAJIDI’S BARAN - Rachmat Nurcahyo (Jurnal Penelitian Humaniora, 2007)
This research aims at exploring the description of male-female relationship in two films, Kiamat Sudah Dekat and Baran. This is a content analysis research. The subjects of this research are Mizwar’s Kiamat Sudah Dekat and Majidi’s Baran. Dta are collected through observing sequences of the films including the scripts and symbols employed. Any action is analyzed on the bases of what is searched by researchers. In this case, the pattern of relation between the main actors who are young Moslems is analyzed. From the various views, the researcher finds the interference of the male-female relation in the films. This result of the research shows the comparison of the representation of young Moslems in facing the problem of love. Baran explores the way a boy, Lateef, expresses his love to Baran. With hard struggle of life among refugees, they express their feeling in their own languages. Kiamat Sudah Dekat explores the way Indonesian Islam rules male-female relationship. With its comical sense, this film tries to send messages to Indonesian youngsters on how Islam views dating among them. Both films tend to explore shots of love problem among young Moslems. These shots are so ideological that watchers are able to catch the imperative matters of the films. This is Islamic identity as to Moslems male-female relationship. This fiction is still and always a depiction of Islamic value